2023
DOI: 10.1002/admi.202202394
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Electron Distribution of Co Nanoparticles Supported on N‐Doped Mesoporous Hollow Carbon Spheres Endows Highly Efficient ORR, OER, and HER

Abstract: The tailoring of the charge transfer between support material and transition metal active phase is an effective strategy for fine tuning the electronic structure of the catalyst active site, and hence improving the activity and stability of the reaction. This works presents that Co nanoparticles supported on N‐doped mesoporous hollow carbon nanospheres (Co/NMHCS) decouple the effect of electronic structure on catalytic performance. The detailed experimental and theoretical results reveal the charge distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Furthermore, the formation of the interface between NMHCS and Co can promote the absorption of OOH*, thus resulting in the optimal performance of the oxygen evolution reaction (OER), oxygen reduction reaction (ORR), and hydrogen evolution reaction (HER). 31 However, how to stably synthesize the transitionmetal−supported @ hollow nanocarbon sphere catalyst with excellent activity is still a difficult problem. Herein, we successfully synthesized well-defined and structurally stable hollow nanocarbon spheres (named the Cnanosphere).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the formation of the interface between NMHCS and Co can promote the absorption of OOH*, thus resulting in the optimal performance of the oxygen evolution reaction (OER), oxygen reduction reaction (ORR), and hydrogen evolution reaction (HER). 31 However, how to stably synthesize the transitionmetal−supported @ hollow nanocarbon sphere catalyst with excellent activity is still a difficult problem. Herein, we successfully synthesized well-defined and structurally stable hollow nanocarbon spheres (named the Cnanosphere).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the special NMHCS structure could provide abundant active sites, promoting the kinetics of the catalytic processes. Furthermore, the formation of the interface between NMHCS and Co can promote the absorption of OOH*, thus resulting in the optimal performance of the oxygen evolution reaction (OER), oxygen reduction reaction (ORR), and hydrogen evolution reaction (HER) . However, how to stably synthesize the transition-metal–supported @ hollow nanocarbon sphere catalyst with excellent activity is still a difficult problem.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Recognizing these limitations, there is a growing interest in three-dimensional (3D) nanocatalysts due to their substantial specific surface area, enhanced site exposure for high activity, and improved mass transfer rates. 13,14 For example, Wei et al synthesized a graphene aerogel catalyst incorporating NiCoP nanoparticles (NiCoP-NPs@GA) that exhibited a slight collapse after 1000 CV cycles. 15 Hence, it is necessary to develop a 3D transition metal phosphide catalyst for electrocatalytic water splitting with high activity and excellent stability.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Despite the advantages of TMP, these electrocatalysts usually suffer from sluggish electron transport, slow electrolyte diffusion, and delayed bubble evolution. Even worse, they are prone to aggregation or structural collapse, resulting in poor long-term catalytic process stability of the catalysts. , Recognizing these limitations, there is a growing interest in three-dimensional (3D) nanocatalysts due to their substantial specific surface area, enhanced site exposure for high activity, and improved mass transfer rates. , For example, Wei et al synthesized a graphene aerogel catalyst incorporating NiCoP nanoparticles (NiCoP-NPs@GA) that exhibited a slight collapse after 1000 CV cycles . Hence, it is necessary to develop a 3D transition metal phosphide catalyst for electrocatalytic water splitting with high activity and excellent stability.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and theoretical results revealed that N-doped MHCS resulted in charge distribution at the Co/NMHCS interface, showing a strong ability to adsorb and reduce OOH* and protons. 23 In addition to the introduction of nitrogen alone, co-doping N and S with different atomic radii and electronegativities can largely change the electron distribution of adjacent carbon atoms, resulting in high ORR activity. 24,25 Yan et al demonstrated that the synergistic interaction of N and S in the carbon skeleton can produce more defects and the p-N/S adsorption potential with oxygen is greatly reduced, promoting the ORR process.…”
Section: Introductionmentioning
confidence: 99%